COVID-19 disease, obesity and micronutrients: an updated narrative review of the literature. Issue 5 (4th November 2020) - Papadopoulou, Sousana K.; Mantzorou, Maria; Koutridou, Desspina; Tassoulas, Elias; Sakellaropoulou, Styliani; Biskanaki, Fani; Xatziapostolou, Efthymis; Papandreou, Dimitrios
Abstract : Purpose: The purpose of this paper is to critically summarize the current data concerning the impact of obesity and micronutrient adequacy and supplementation on the risk and severity of COVID-19 disease, and their potential impact on treatment and rehabilitation. Design/methodology/approach: PubMed, Scopus and Google Scholar databases were thoroughly searched to identify studies concerning obesity and nutritional status, vitamin and other micronutrients adequacy with COVID-19 severity. Findings: Individuals with higher body mass index are in greater risk of severe disease and need for mechanical ventilation. Concerning micronutrient adequacy, no published studies at the present time have evaluated the effect of supplementation on the risk and the treatment of the novel disease. Originality/value: Recently, COVID-19 has monopolized the interest of the medical community regarding diet and nutritional status and it possibly plays an important role in disease severity.